Non-specific immunostimulatory capacity of Newcastle disease virus (NDV) and suppression of breast cancer cells - Ahmed, Ismaila; Ahmad, Umar; Othman, Fauziah; Yong, Yoke Keong (International Journal of Pharmaceutical and Clinical Research, 2014)
Newcastle disease virus (NDV) is an enveloped single stranded RNA virus that causes deadly infection to over 250 species of birds, comprising domestic and wild-type, thus resulting in substantial economic loss to poultry industry across the globe. NDV possesses several distinctive properties that make it an outstanding anti-cancer agent. In humans it is reported to have oncolytic and immune-stimulatory effects, precisely replicates in tumour cells while sparing normal cells and causes oncolysis. Although NDV has been extensively studied by researchers there is still need for a vigorous research on its potential use as a new treatment modality to cancer patients through a known process termed viroimmunotherapy. This paper deals with an overview of the research which has been carried out worldwide in the use of immune-stimulatory properties of NDV as an anti-cancer agent.